CONCEPT SELECTION STORAGE FACILITY, REGASIFICATION FACILITY, AND STATION KEEPING SYSTEM OF LNG ON EXSISTING PLATFORM AND OFFSHORE LOCATION - Desintya Ramadani, Dinda
This final project aims to select the most technically and economically efficient concept for the storage regasification facility and the station keeping system for the LNG FSRU, at both the existing platform location and Location X, in response to the expiration of the West Java FSRU lease. The urgency of this project is driven by the vital role of the FSRU in supplying gas for power plants in Jakarta Bay and the increasing electricity consumption, which requires expansion of LNG infrastructure. This study also examines the utilization of unused platforms to enhance capacity and efficiency. The methodology includes a technical analysis of structural offset and the operability limits of the Marine Loading Arm (MLA) based on environmental data, along with a financial analysis of capital expenditure (Capex) and operational expenditure (Opex). The technical analysis involves static and dynamic simulations to assess the structural offset in relation to environmental conditions such as waves, currents, and wind. Additionally, the operability limit of the MLA is evaluated to determine operational constraints in LNG transfer. In the financial analysis, Capex is calculated based on the initial costs of construction or acquisition of the facility, while Opex covers ongoing operational costs. Various scenarios are tested to determine the optimal configuration. The results show that the offshore location with FSRU storage and regasification facilities and a cross berth mooring structure (dolphin structure) is the most economical and efficient option, as it has the lowest cost of 421.85 million US dollars with a low and high price estimate difference of 9%, the smallest offset of 0.78 meters, and the best MLA operational limit, which is ship to deck at the offshore location.